Impact of deep learning on pediatric elbow fracture detection: a systematic review and meta-analysis. - Binh, Le Nguyen; Nhu, Nguyen Thanh; Nhi, Pham Thi Uyen; Son, Do Le Hoang; Bach, Nguyen; Huy, Hoang Quoc; Le, Nguyen Quoc Khanh; Kang, Jiunn-Horng (European Journal of Trauma & Emergency Surgery, 2025)
Objectives: Pediatric elbow fractures are a common injury among children. Recent advancements in artificial intelligence (AI), particularly deep learning (DL), have shown promise in diagnosing these fractures. This study systematically evaluated the performance of DL models in detecting pediatric elbow fractures. Materials and methods: A comprehensive search was conducted in PubMed (Medline), EMBASE, and IEEE Xplore for studies published up to October 20, 2023. Studies employing DL models for detecting elbow fractures in patients aged 0 to 16 years were included. Key performance metrics, including sensitivity, specificity, and area under the curve (AUC), were extracted. The study was registered in PROSPERO (ID: CRD42023470558). Results: The search identified 22 studies, of which six met the inclusion criteria for the meta-analysis. The pooled sensitivity of DL models for pediatric elbow fracture detection was 0.93 (95% CI: 0.91–0.96). Specificity values ranged from 0.84 to 0.92 across studies, with a pooled estimate of 0.89 (95% CI: 0.85–0.92). The AUC ranged from 0.91 to 0.99, with a pooled estimate of 0.95 (95% CI: 0.93–0.97). Further analysis highlighted the impact of preprocessing techniques and the choice of model backbone architecture on performance. Conclusion: DL models demonstrate exceptional accuracy in detecting pediatric elbow fractures. For optimal performance, we recommend leveraging backbone architectures like ResNet, combined with manual preprocessing supervised by radiology and orthopedic experts.